Андрієвський – активний громадський діяч та просвітник на теренах України - Підвальна, Юлія Олексій; Pidvalna, Julia (My University, 2014)
У статті проаналізовано один із важливих напрямів життєдіяльності О. Андрієвського – активна громад-ська та просвітницька справа на теренах України в другій половині ХІХ ст. Установлено, що вчений зробив великий внесок у розвиток народної освіти, а просвітницько-громадська діяльність була незмінно спрямована на покращення та підвищення української культури.В статье проанализировано одно из важных направлений жизнедеятельности О. Ан-дриевского – активная общественная и просветительская деятельность на территории Украины во второй половине ХІХ ст. Установлено, что ученый внес большой вклад в развитие народного образования, а просве-тительско-общественная деятельность была неизменно направлена на улучшение и повышение украинской культуры. О. Андриевский вошел в историю нашего государства не только как талантливый педагог, но и как активный общественный деятель, просветитель. О. Андриевский играл очень важную роль в одесской общине. Считалось, что идеологом этого общества был Л. Смоленский, а организатором конкретных дел – О. Андриевский.In the article examines one of the most important areas of life A. Andriyevskiy – active social and education al affairs in the territory of Ukraine in the second half of the nineteenth century. It was established that the scientist has made a great contribution to the development of public education, and educational and social activities was invariably directed at improving and increasing the Ukrainian culture. A. Andriyevskiy entered into the history of our country not only as a gifted teacher, but also as an active social activist, educator, who «heard by beating the Public Pulse» and quickly with all their «language to the children and people in general», responded to it. A. Andriyevskiy played a very important role in the Odessa community thought that this society was the ideologue L. Smolensky and organized individual cases − A. Andriyevskiy. Andriyevskiy life was a man who tried always and everywhere to give their ideas and actual implementation developed in these cases boundless energy. Aleksey Aleksandrovich Andryevskyy – active worker of educational nature.
Alex Andriyevskiy − an Active Commu nity Leader and Educator in the Ukraine.
Keywords: О. Андрієвський, активний громадський діяч, освіта, культура, просвітницька діяльність; О. Андриевский, активный общественный деятель, просветитель.; O. Andrievskiy, anactive public figure, anenlightener.